1999
DOI: 10.1080/103491299100759
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Relationship Between the Efficacy of Training Programs and the Work Environment for Workers with Disabilities

Abstract: The purpose of the study was to test a structural model which involves training variables and work environment variables in the U nited Arab Emirates andJordan. Two instrum ents were used to collect data from people with a disability (n 5 113) about their views of the training program and work environm ent. The Structural Equation M odel (SEM ) analysis revealed the following results: the factor representing psychological support and suitability of training environment in¯uenced positively the disabled workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A study suggests, however, that employment, especially work in the competitive workforce, may be a significant source of enhancing adaptive skills for people with such disabilities and, thus, greatly adding to the success of community living (Stephens, Collins & Dodder, 2005, p. 469). Sartawi, Abu‐Hilal and Ibrahim Qaryouti (1999), however, explored the issue of people with disability and how they are perceived in the UAE. His study showed that job selection, if the person was employed, had a direct negative effect on how others perceive the disabled person.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A study suggests, however, that employment, especially work in the competitive workforce, may be a significant source of enhancing adaptive skills for people with such disabilities and, thus, greatly adding to the success of community living (Stephens, Collins & Dodder, 2005, p. 469). Sartawi, Abu‐Hilal and Ibrahim Qaryouti (1999), however, explored the issue of people with disability and how they are perceived in the UAE. His study showed that job selection, if the person was employed, had a direct negative effect on how others perceive the disabled person.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Additionally, it has been stated that Arab communities, whether based in the Middle East or as part of a global diaspora, regard disability as a stigmatizing condition that affects the entire family (Atshan, 2007; Boukhari, 2007; Sharifzadeh, 1998; Westbroook and Legge, 1993). It is therefore argued that stigma deters research into disability and consequently accurate data is hard to gather in Arab states (Dinero, 2002; Sartawi et al, 1999). Dinero (2002) adds that with regards to research among Palestinians the drawing up of public records of families with disabled relatives is an inhibitory factor to disclosure due to mistrust of State interests.…”
Section: Reflections On the Ethical Implications Of Research In Arab Societiesmentioning
confidence: 99%